Dakwah Anti Kriminalitas Pada remaja Melalui Bimbingan Konseling Pelajar Yang Terlibat Tawuran - Laili Rahmawati, Alfi; Sarah, Aeni; Tri Darmaninghrum, Khaerunnisa; Janah, Khulatul (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This study aims to analyze the implementation of anti-criminality preaching for teenagers through counseling for students involved in brawls. Student brawls are a form of criminal behavior that frequently occurs among teenagers, which can have a negative impact on their personal and social development. Anti-criminality preaching plays an important role in providing moral and ethical understanding that can shape the character of adolescents, helping them avoid negative behaviors, including brawling. This research uses a qualitative approach with a case study method, involving students who have been involved in brawls as the subjects of the study. Data collection techniques were carried out through interviews, observations, and documentation. The results show that counseling combined with anti-criminality preaching can have a positive impact on changing the attitudes and behaviors of adolescents by increasing their awareness of the negative consequences of brawling and strengthening their commitment to avoid criminal actions. This study is expected to contribute to efforts in preventing brawls and shaping better adolescent character through an adaptive and effective preaching approach.